A Multicore Load Balancing Model Based on Java NIO - Yang Wang; Guofeng Qin (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
First this paper points out two common problems of utilizing processors under multicore architecture, namely processors waiting for IO operation to finish and load balancing among cores. Then it makes an analysis of the reasons for them. In order to fully exploit multicore processors, this paper proposes a multicore load balancing model based on the Java NIO framework which offers a solution to above problems. This model mainly illustrates a task scheduling algorithm which uses a parallel computing framework, Java Fork/Join. At last, experiments and performance analysis prove the effectiveness of this model in utilizing the multicore processors. Although the model is constructed under the architecture of Java language, it can be extended to other languages without much being changed. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1431